2020
DOI: 10.21203/rs.3.rs-70833/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Metabolomics Study on Improvement of Mild Cognitive Impairment by SCPE: a  UPLC-Q/TOF-MS Mass Spectrometric Study

Abstract: Background: Mild Cognitive Impairment (MCI) is a common and easilyneglected neurological disease in clinic. Aging is the main cause of the disease,but its exact pathogenesis is not yet clear. Sagacious Confucius' PillowElixir(SCPE) is a classic medicine for the treatment of amnesia in traditionalChinese medicine.The aim of this study was to prove the stability and reliabilityof SAMP8 mice as MCI model, and to nd potential biomarkers for thetransformation of mild cognitive impairment to dementia, so as to revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Both EMCI-2 and LMCI-2 also show higher activation of the aminoacyl-tRNA biosynthesis. However, the activity of Aminoacyl-tRNA as it relates to AD disease progression is complex and not well understood (Kron, 2013), although numerous studies have mentioned this pathway in their results (Trushina, 2013;Wang, 2020;Hou, 2020). A suppressed zinc ion binding pathway, on the other hand, has been linked to oxidative stress by means of lipid peroxidation, an increase in osmotic fragility of erythrocyte membranes, and a decrease in protein turnover (Jurowski, 2014;Roohani, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Both EMCI-2 and LMCI-2 also show higher activation of the aminoacyl-tRNA biosynthesis. However, the activity of Aminoacyl-tRNA as it relates to AD disease progression is complex and not well understood (Kron, 2013), although numerous studies have mentioned this pathway in their results (Trushina, 2013;Wang, 2020;Hou, 2020). A suppressed zinc ion binding pathway, on the other hand, has been linked to oxidative stress by means of lipid peroxidation, an increase in osmotic fragility of erythrocyte membranes, and a decrease in protein turnover (Jurowski, 2014;Roohani, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the NLRP3 and downstream inflammatory signaling pathways can be activated by the CGAS-STING signaling [20,21]. It is reported that aging-related cerebral infarction is alleviated by EA through downregulating the NLRP3/Caspase-1 signaling [22]. Currently, the regulatory relationship between CGAS-STing-NLRP3 signaling axis and depression has not been clarified.…”
Section: Introductionmentioning
confidence: 99%